Future of DAQ Frameworks and Approaches, and Their Evolution towards the Internet of Things. Issue 8 (December 2015) - Neufeld, Niko
Abstract: Nowadays, a DAQ system is a complex network of processors, sensors and many other active devices. Historically, providing a framework for DAQ has been a very important role of host institutes of experiments. Reviewing evolution of such DAQ frameworks is a very interesting subject of the conference. "Internet of Things" is a recent buzz word but a DAQ framework could be a good example of IoT.